Pengembangan model pembelajaran active learning dengan media worwall untuk meningkatkan hasil belajar bahasa Arab siswa - Agustar, Agustar; Zahrah, Humairatuz (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2025)
This study aims to develop an active learning model in Arabic language education using wordwall media to enhance student’s learning outcomes. The research method employe dis Research and Development (R&D) with the ADDIE development model which includes analysis, design, development, implementation, and evaluation. Wordwall media was utilizied to support interactive learning through various engaging game features, such as quizzes and interactive cards designed to boost student’s motivation and participation. The study’s subjects were fifth-grade students at Pondok Pesantren Salafiyah Ula Imam Syafi’i Batam. The result showed that using the active learning model based on wordwall significantly improved student’s understanding and activeness in learning Arabic, especially on the في المدرسة topic. This research contributes to the development of technology-based learning innovation in education.